Researches of a scanner opportunity for photographic plates processing and astrometric and photometric data gaining - M. T. Pogoreltsev (Вісник Астрономічної школи, 2004)
Researches of an opportunity of use in the astrometric purposes of the digital images of photographic plates received by the scanner ScanMaker-4 manufactured by Microtec were carried out by the authors. Photographic plates with the images of star fields received with different telescopes were used for research. The processing of digital images of photoplates was made with the ESO-MIDAS and with the programs developed by one of the authors. The researches have shown, that this technology provides results with acceptable quality level. That makes possible use of the given scanner for mass processing of the stored photographic material.